Removal of methylene blue from aqueous solution by sewage sludge-derived biochar: Adsorption kinetics, equilibrium, thermodynamics and mechanism. Issue 1 (February 2017) - Fan, Shisuo; Wang, Yi; Wang, Zhen; Tang, Jie; Tang, Jun; Li, Xuede
Graphical abstract: Highlights: Municipal sludge was prepared to biochar. Adsorption kinetic was described by the pseudo-second order model. Equilibrium data were well fitted to the Langmuir isotherm equation. The adsorption mechanism includes electrostatic interaction, ion exchange, hydrogen bond interaction, n- π interaction. Abstract: In this study, biochar was produced from municipal sludge and was characterized by Surface area and porosity analysis, Scanning Electron Microscope–Energy Dispersive Spectrometer (SEM-EDS) and Fourier Transform Infrared Spectroscopy (FTIR). The effect factors including adsorbent dosage, contact time, pH, temperature on the adsorption properties of methylene blue (MB) from aqueous solution onto sludge-derived biochar were investigated in batch experiments. The adsorption kinetics, isotherm, thermodynamic and mechanism were also studied. The results showed that the adsorption kinetics of MB on biochar was accurately described by a pseudo-second-order model, indicating that liquid film diffusion, intra-particle diffusion and surface adsorption coexisted during MB adsorption on the biochar. The equilibrium adsorption data were well represented by the Langmuir isotherm equation ( R 2 > 0.99). As the initial MB concentration and temperature increased, the adsorption amount also increased and the adsorption was favorable. The thermodynamic analysis showed that MB adsorption onto sludge-derived biochar was spontaneous and endothermic. The desorption and reusability experiment indicated that sludge-derived biochar had the potential to be a reusable adsorbent for MB removal.The adsorption mechanism appeared to be related to electrostatic interaction, ion exchange, hydrogen bond interaction, n- π interaction, etc. Thus, sludge-derived biochar can be used as an effective absorbent to remove dyes from wastewater. As a beneficial by-product of sludge, sludge-derived biochar also can mitigate the environmental burden of sewage sludge.